Implementation of digital technologies in the optimization of material and technical support of construction projects - Horbach, M.; Basanskyi, V.; Kolomiiets, V.; Naumenko, Y.; Herasymchuk, O. (Ways to Improve Construction Efficiency, 2024)
The implementation of digital technologies in the system of material and technical support of construction projects is a key vector of development in the modern construction industry. Resource supply processes lose efficiency under traditional approaches, when delays in deliveries, duplication of information, discrepancies between actual needs and planned volumes, and lack of systematic control occur. The use of digital tools opens up new opportunities for optimizing these processes, reducing costs, and increasing transparency across the entire supply chain. The application of ERP solutions, supply chain management (SCM) systems, cloud services, and artificial intelligence technologies makes it possible to integrate all stages – from procurement planning to the accounting of used materials – into a unified information space. This creates conditions for effective interaction between suppliers, contractors, and clients, reduces transaction costs, and ensures timely responses to changes in the project environment. Particular importance lies in the use of big data analytics and intelligent forecasting algorithms. These tools make it possible to determine optimal procurement volumes, assess potential risks of resource shortages, model scenarios of development, and monitor the execution of logistics operations in real time. As a result, not only the speed of management decision-making increases, but also their accuracy, which is of strategic importance in the highly competitive construction market. The integration of digital technologies contributes to the creation of resilient and flexible digital ecosystems, where material and technical supply costs are considered as investments capable of generating long-term added value. Proper organization of these processes allows not only the reduction of unproductive expenses, but also the increase of overall company productivity, improvement of construction product quality, and minimization of the risks of missed deadlines. Optimization of material and technical support with the help of digital tools shapes a new culture of resource management in construction companies. Resources are viewed not as a cost item, but as a strategic factor in ensuring the sustainability and development of the enterprise.